(x+1)+(x+2)+(2x+1)=2

Simple and best practice solution for (x+1)+(x+2)+(2x+1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)+(x+2)+(2x+1)=2 equation:


Simplifying
(x + 1) + (x + 2) + (2x + 1) = 2

Reorder the terms:
(1 + x) + (x + 2) + (2x + 1) = 2

Remove parenthesis around (1 + x)
1 + x + (x + 2) + (2x + 1) = 2

Reorder the terms:
1 + x + (2 + x) + (2x + 1) = 2

Remove parenthesis around (2 + x)
1 + x + 2 + x + (2x + 1) = 2

Reorder the terms:
1 + x + 2 + x + (1 + 2x) = 2

Remove parenthesis around (1 + 2x)
1 + x + 2 + x + 1 + 2x = 2

Reorder the terms:
1 + 2 + 1 + x + x + 2x = 2

Combine like terms: 1 + 2 = 3
3 + 1 + x + x + 2x = 2

Combine like terms: 3 + 1 = 4
4 + x + x + 2x = 2

Combine like terms: x + x = 2x
4 + 2x + 2x = 2

Combine like terms: 2x + 2x = 4x
4 + 4x = 2

Solving
4 + 4x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 4x = 2 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 2 + -4
4x = 2 + -4

Combine like terms: 2 + -4 = -2
4x = -2

Divide each side by '4'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 4y-7+y+33=6y+30-3y | | 9x-5x=516 | | 5x^3-x^2+25x-5= | | 2x+3x-11=66 | | 5x+57=x+15 | | 2x^3-12x^2-30x+1=0 | | -(j+9)+-13j+12= | | f=11hg | | (R-9)3-12=33 | | 0.26(10000)-0.02=0.08(y+10000) | | 32=9+2 | | ax^2+3x+1=0 | | 32=9+2W | | 5x-x=444 | | f(x)=5x^2-x+9 | | Us+us=r | | 2b+10= | | -10w=s | | 20-4p=5+3p | | 0=5x^2-x+9 | | 4.05p+14.40=4.50p+7.5 | | 31=3(2x-1)+4 | | -5x-10=6x-8 | | 5x+1=120 | | 4(x+3x)=12 | | x+y=-320 | | 39v^2+10v=0 | | 8.5=-1.5y | | 60+.70m=30+.80m | | x^2+2.8=3.2 | | (7x^2)+14x=0 | | -6(x+4)-43=7-38 |

Equations solver categories